Efecto de la época y el pastoreo sobre el valor nutritivo potencial del pasto estrella (Cynodon nlenfuensis, Vanderyst) (ING) - Arroyo, Rafael (1987)
A grazing experiment was conducted at “Santa Lucía” Research Farm, Heredia, Costa Rica, on African Star Grass (Cynodon nlenfuensis, Vanderyst) from July 1982 to December 1983. The pastures were established in 1979 on a Typic Dystrandept soil. The annual precipitation for the region was 2000 mm and 19.7°C annual average temperature. The stand received 150kg of N/ha in even applications after each grazing during the rainy season. The animals were rotated in a system with 3-d grazing period and 28-d or 35-d rest period for the rainy and dry season, respectively, with a stocking rate of 3.5 AU/ha. Crude protein (% CP), dry matter (%DM), Neutral detergent fiber (%NDF) and in vitro dry matter digestibility were analyzed (IVDMD). The results showed that %CP. %DM and IVDMD were affected significantly (P≤0.05) by season and grazing (before/after) NDF was affected by grazing but not by season. Based upon this experience it is recommended, to study optimum defoliation rates and adequate grazing and rest period in order to achieve maximum voluntary intake by the grazing herd through the year.